The Bank Lending Channel of Monetary Policy? The Panel Evidence from Egypt - Shokr, Mohamed Aseel; Karim, Zulkefly Abdul; Jusoh, Mansor; Zaidi, Mohd. Azlan Shah Shah (Gadjah Mada International Journal of Business, 2014)
This paper examines the relevance of the bank lending channel of monetary policy in Egypt using bank-level data. Previous empirical studies in Egypt that used macro-level data have not supported the relevance of the bank lending channel. However, using a sample of 32 commercial banks for the period from 1998 until 2011 and a dynamic panel GMM technique, the empirical findings revealed the relevance of the bank lending channel of monetary policy in Egypt. Moreover, there is a heterogeneity effect of monetary policy on bank loans according to bank size, in which the small banks are more affected during a monetary contraction than larger banks. This finding signals that the monetary authorities in Egypt should take cognizance of the stability of interest rates in order to stabilize the bank loan supply.